Problematization of the complexity of thought systems: an epistemological model for empirical research on paradigms - Rodríguez Zoya, Leonardo Gabriel (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2017)
This paper revisits one of the most relevant aspects of Edgar Morin’s work: the problematization of paradigms and organization of thought systems. Likewise, the paper elaborates a strategy for overcoming one of the stronger limitations of its work: the lacks of an empirical methodology to develop the complex thought in the domain of scientific research. This paper is organized as follows. First, we problematize the complexity of thought systems. Second, we propose and develop the category of complex problems. Finally, we outline an epistemological model for empirical research on paradigms.